2014
DOI: 10.3109/13685538.2014.967672
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the bladder wall thickness on the outcome of the medical treatment using alpha-blocker of BPH patients with LUTS

Abstract: BWT has positive correlation with the total IPSS, voiding symptoms subscores and storage symptoms subscores. The response to medical treatment is found statistically less in patients with BWT greater than 5 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…They found statistically significantly greater improvement in these values in the group with BWT <5 mm. Therefore, it was emphasized that BWT could be evaluated in determining the response to medical treatment (11). In their study, Karaköse et al reported that BWT was significantly lower after alpha-blocker treatment.…”
Section: Discussionmentioning
confidence: 99%
“…They found statistically significantly greater improvement in these values in the group with BWT <5 mm. Therefore, it was emphasized that BWT could be evaluated in determining the response to medical treatment (11). In their study, Karaköse et al reported that BWT was significantly lower after alpha-blocker treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated the effects of pharmacologic treatment for BPO on BWT. Treatment with α‐blockers has been shown to significantly reduce BWT in various studies . De Nunzio et al evaluated the effect of dutasteride add‐on therapy in patients with 27 “BPH” already being treated with α‐blockers .…”
Section: When and Under Which Circumstances Is The Recovery Of The Blmentioning
confidence: 99%
“…Treatment with α-blockers has been shown to significantly reduce BWT in various studies. [37][38][39] De Nunzio et al 40 evaluated the effect of dutasteride add-on therapy in patients with 27 "BPH" already being treated with α-blockers. 40 After 24 weeks of treatment, they observed a significant reduction in DWT.…”
Section: Circumstances Is the Recovery Of The Bladder Possible After mentioning
confidence: 99%